2021
DOI: 10.2196/26406
|View full text |Cite
|
Sign up to set email alerts
|

Central Auditory Tests to Track Cognitive Function in People With HIV: Longitudinal Cohort Study

Abstract: Background The development of neurocognitive deficits in people infected with HIV is a significant public health problem. Previous cross-sectional studies have shown that performance on central auditory tests (CATs) correlates with cognitive test results in those with HIV, but no longitudinal data exist for confirmation. We have been performing longitudinal assessments of central auditory and cognitive function on a cohort of HIV-positive and HIV-negative individuals in Dar es Salaam, Tanzania to u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 78 publications
1
16
0
1
Order By: Relevance
“…While these effects were statistically reliable, their small magnitude means that they are unlikely to account for the higher incidence of hearing complaints among PLWH. Central auditory processing and aural cognition may contribute to these hearing difficulties, as shown in previous studies 2,8,9 . Still, this study indicates a subclinical difference in peripheral auditory function in young individuals living with HIV.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…While these effects were statistically reliable, their small magnitude means that they are unlikely to account for the higher incidence of hearing complaints among PLWH. Central auditory processing and aural cognition may contribute to these hearing difficulties, as shown in previous studies 2,8,9 . Still, this study indicates a subclinical difference in peripheral auditory function in young individuals living with HIV.…”
Section: Discussionsupporting
confidence: 72%
“…Central auditory processing and aural cognition may contribute to these hearing difficulties, as shown in previous studies. 2,8,9 Still, this study indicates a subclinical difference in peripheral auditory function in young individuals living with HIV. Future work aims to continue following these individuals to determine if the early signs of dysfunction augur subsequent clinical hearing loss.…”
Section: Discussionmentioning
confidence: 55%
“…Central auditory function, reflected in tests of speech perception in background noise, correlates with cognition (Watson, 1991;Hallgren et al, 2001;Anderson and Kraus, 2010;Hoover et al, 2017;Panza et al, 2018;Danielsson et al, 2019;Humes, 2020Humes, , 2021, including cognitive dysfunction due to mild cognitive impairment (MCI), Alzheimer's disease (Gates et al, 1996;Idrizbegovic et al, 2011), and HIV (Zhan et al, 2017b;Buckey et al, 2019;White-Schwoch et al, 2020;Niemczak et al, 2021). This suggests central auditory tests might be useful for tracking cognitive dysfunction in populations with disordered neuro-cognitive processing.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between central auditory function and cognition suggests that auditory information is not only processed by the cochlea and auditory pathway, but also by other associative cortical areas (Harris et al, 2012;Palmer and Musiek, 2014;Sardone et al, 2019;Song et al, 2020). Our previous work has shown a relationship between central auditory test performance and cognitive performance, which suggested that central auditory tests might be useful for tracking cognitive performance in people living with HIV (PLWH) (Maro et al, 2014;Zhan et al, 2018;Buckey et al, 2019;Niemczak et al, 2021). The goal of this study was to evaluate the relationship between central auditory tests and neurocognitive domains in adults living with HIV and HIV-negative (HIV-) controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation